Hubungan Motivasi Belajar dan Perhatian Orang Tua dengan Kesiapan Belajar Siswa Kelas V SD Harapan Indonesia Bekasi - Rakim; Suroyo (PARAMETER, 2021)
Learning motivation and parental attention are important things in increasing student learning readiness. The purpose of this study was to determine how big the influence and relationship between learning motivation and parental attention on the learning readiness of fifth-grade students of SD Harapan Indonesia. Data was collected through a sample to represent the entire population and data collection using a questionnaire. The method used is the descriptive method with data collection through questionnaires and observation. The results of the T-test showed that there was a positive relationship between learning motivation and learning readiness of fifth-grade students at Harapan Indonesia Elementary School Bekasi with a strong relationship level, there was a positive relationship between parental attention and learning readiness of fifth-grade students at Harapan Indonesia Elementary School Bekasi, with a moderate level of relationship. There is a positive relationship between learning motivation and parental attention together with the learning readiness of fifth-graders at SD Harapan Indonesia Bekasi with a moderate level of relationship. Abstrak Motivasi belajar dan perhatian orang tua merupakan hal yang penting dalam meningkatkan kesiapan belajar siswa. Tujuan dari penelitian ini adalah untuk mengetahui seberapa besar pengaruh dan hubungan antara motivasi belajar dan perhatian orang tua dengan kesiapan belajar siswa kelas V SD Harapan Indonesia. Data dikumpulkan melalui sampel untuk mewakili seluruh populasi dan pengumpulan data menggunakan kuesioner. Metode yang digunakan adalah metode deskriptif dengan pengumpulan data melalui angket dan observasi. Hasil uji T menunjukkan adanya hubungan yang positif antara motivasi belajar dengan kesiapan belajar siswa kelas V SD Harapan Indonesia Bekasi dengan tingkat hubungan kuat, ada hubungan yang positif antara perhatian orang tua dengan kesiapan belajar siswa kelas V SD Harapan Indonesia Bekasi, dengan tingkat hubungan sedang. Terdapat hubungan yang positif antara motivasi belajar dan perhatian orang tua secara bersama-sama dengan kesiapan belajar siswa kelas V SD Harapan Indonesia Bekasi dengan tingkat hubungan sedang.